2019
DOI: 10.9734/ajrb/2019/v5i230084
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic Potential of Ethanolic Leaf Extract of Talinum triangulare in Wistar Rats

Abstract: Aim: This study focuses on assessing the haematopoietic potential of ethanolic extract of Talinum triangulare leaves in Wistar rats. Methods: Fresh plants of T. triangulare were purchased from a local market in Orita-Challenge area of Ibadan, Nigeria. They were air dried at room temperature in an open laboratory space for 21 days and milled into powder. The extraction was done using soxhlet apparatus and ethanol as the solvent. The ethanol was evaporated in a rotary evaporator at 35°C with a yield of 2.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…The augmented level of liver biomarkers is the key indication of liver injury. The current study concluded that pretreatment with moringa significantly restored these elevations due to its high antioxidant potential and its ability to scavenge free radicals ( 45 ). Similar outcomes were mentioned by Islam and Alam ( 46 ), where the protective activity of M. oleifera Lam.…”
Section: Discussionmentioning
confidence: 72%
“…The augmented level of liver biomarkers is the key indication of liver injury. The current study concluded that pretreatment with moringa significantly restored these elevations due to its high antioxidant potential and its ability to scavenge free radicals ( 45 ). Similar outcomes were mentioned by Islam and Alam ( 46 ), where the protective activity of M. oleifera Lam.…”
Section: Discussionmentioning
confidence: 72%
“…When compared to the normal control, rats intoxicated with potassium bromate had raised levels of creatinine, urea, and uric acid-all crucial nephrotic indicators. Renal illness is characterised by severe liver disease with cell death that impairs the urea cycle and results in decreased glomerular filtration, retention of urea, and urea excretion [38]. Kidney impairment is indicated by a build-up of creatinine in the blood [39].…”
Section: Discussionmentioning
confidence: 99%
“…The filtrate was subsequently evaporated to dryness using a rotary evaporator at 45°C. Before usage, the extract was collected into an air tight container and refrigerated (Airaodion et al, 2019).…”
Section: Preparation Of Extractmentioning
confidence: 99%